2020
DOI: 10.1007/s00701-020-04529-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of posttraumatic syringomyelia: evidence from a systematic review

Abstract: Background Following spinal cord injury (SCI), the routine use of magnetic resonance imaging (MRI) resulted in an incremental diagnosis of posttraumatic syringomyelia (PTS). However, facing four decades of preferred surgical treatment of PTS, no clear consensus on the recommended treatment exists. We review the literature on PTS regarding therapeutic strategies, outcomes, and complications. Methods We performed a systematic bibliographic search on (“spinal cord injuries” [Mesh] AND “syringomyelia” [Mesh]). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…However, a recent systematic review concluded that "no satisfactory standard treatment exists". 26 We hypothesize that transplantation of neural stem and progenitor cells in conjunction with surgical treatment results in higher efficacy. In our previous study, we demonstrated that human NPCs derived either from prenatal tissue or iPSCs (i.e., NESCs) effectively reversed intraspinal cyst expansion in a rat model of PTS, 15 but if these transplanted cells can also achieve tissue repair has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review concluded that "no satisfactory standard treatment exists". 26 We hypothesize that transplantation of neural stem and progenitor cells in conjunction with surgical treatment results in higher efficacy. In our previous study, we demonstrated that human NPCs derived either from prenatal tissue or iPSCs (i.e., NESCs) effectively reversed intraspinal cyst expansion in a rat model of PTS, 15 but if these transplanted cells can also achieve tissue repair has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, several hypothetical theories have been postulated to explain the development of syringomyelia [ 3 , 11 ]. Syringomyelia has been associated with non-infectious inflammatory lesions [ 12 ]. Hypotheses on the pathophysiology of non-infectious inflammation-associated syringomyelia include coincidence, necrosis, or ex-vacuum central canal dilation due to myelin/axonal damage [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of SLE and syringomyelia in this patient may be coincidental, as syringomyelia is becoming more prevalent and can be discovered incidentally as a result of the increased use of MRI in the routine evaluation of back and neck pain [ 12 ]. It is possible that the autoimmune inflammation associated with SLE contributes to the formation of syrinxes.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty exists regarding the management of PS and a recent meta-analysis identified that the past four decades have failed to produce a consensus regarding its treatment [16]. Similarly, a consensus panel agreed that the evidence was poor but suggested detethering with dural expansion as a first treatment strategy for PSCT and PS [9].…”
Section: Introductionmentioning
confidence: 99%